Analysis of composite wing structures with a morphing leading edge - Morishima, Ryoko (Cranfield University, 2011)
One of the main challenges for the civil aviation industry is the reduction of its environmental impact. Over the past years, improvements in performance efficiency have been achieved by simplifying the design of the structural components and using composite materials to reduce the overall weight. These approaches however, are not sufficient to meet the current demanding requirements set for a „greener‟ aircraft. Significant changes in drag reduction and fuel consumption can be obtained by using new technologies, such as smart morphing structures. These concepts will in fact help flow laminarisation, which will increase the lift to drag ratio. Furthermore, the capability to adapt the wing shape will enable to optimise the aerodynamic performance not only for a single flight condition but during the entire mission. This will significantly improve the aircraft efficiency. The current research work has been carried out as part of the European Commission founded Seventh Framework Program called „Smart High Lift Device for the Next Generation Wing‟ (SADE), which main aim is to develop and study morphing high lift devices. The author‟s investigation focused on developing a design concept for the actuation mechanism of a morphing leading edge device. A detailed structural analysis has been carried out in order to demonstrate its feasibility.In the first phase of the research the attention was directed on the preliminary design and analysis of the composite wing box. The parameters of the key structural components, such as skin, spars, ribs and stringers were set to satisfy the static stress and buckling requirements. Moreover, numerical and experimental studies were conducted to analyse the static failure and buckling behaviour of two typical composite wing structural components: a spar section and a web and base joint assembly. In the second stage of the research, a design for the morphing leading edge actuation mechanism was developed. The actuation system was designed in such a way that the target shape was reached with minimum actuation force demand. A geometrical nonlinear FE analysis was conducted to simulate the leading edge morphing deflection and ensure that structural strength requirements were satisfied. Furthermore, the behaviour of the skin integrated with the internal actuation mechanism was modelled under the aerodynamic pressure, at different flight conditions and gust loads, in order to prove that the proposed actuation system can compete with the conventional rigid rib. This study demonstrated that a feasible morphing leading edge design for a next generation large aircraft wing can be achieved. Developing the readiness of this technology will have a significant impact on aircraft efficiency and considerable contribution towards a more environmental friendly aviation.